2021
DOI: 10.1038/s41598-021-94776-3
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric Lactobacillus plantarum (Lactiplantibacillus plantarum) strains exhibit bile salt hydrolysis, hypocholestrolemic and probiotic capabilities in vitro

Abstract: Lactobacillus plantarum (renamed as Lactiplantibacillus plantarum) has been isolated from many sources but very rarely from rhizospheric soil. This is the first report on isolation and assessment of probiotic capabilities of L. plantarum strains isolated from rhizospheric soil. The isolates were confirmed by 16S rRNA gene sequencing and named as NS14, NS16 and NGG. All the isolates were evaluated for bile salt hydrolysis, hypocholestrolemic potential and probiotic attributes. Our results indicated that all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
(43 reference statements)
3
15
0
Order By: Relevance
“…This suggests that, contrary to previously held opinion (Tanaka et al 1999;Begley et al 2006), presence of bile acids may be no sine qua non for the successful isolation of BSH-active Lactobacillaceae from a given ecosystem. This assertion is supported by reports of Singhal et al (2021) who, most unexpectedly, reported isolating highly BSH-active, hypocholestorelemic, probiotic-capable Lactobacillaceae from rhizospheric soils in India. Free-living bacteria isolated from marine sediments (Methanosarcina acetorum) and Antarctica lakes (Planococcus antarticus) have, most unexpectedly, been reported to also synthesize BSH (Jones et al 2008).…”
Section: Quantitative Assessment Of Bile Salt Hydrolasessupporting
confidence: 59%
“…This suggests that, contrary to previously held opinion (Tanaka et al 1999;Begley et al 2006), presence of bile acids may be no sine qua non for the successful isolation of BSH-active Lactobacillaceae from a given ecosystem. This assertion is supported by reports of Singhal et al (2021) who, most unexpectedly, reported isolating highly BSH-active, hypocholestorelemic, probiotic-capable Lactobacillaceae from rhizospheric soils in India. Free-living bacteria isolated from marine sediments (Methanosarcina acetorum) and Antarctica lakes (Planococcus antarticus) have, most unexpectedly, been reported to also synthesize BSH (Jones et al 2008).…”
Section: Quantitative Assessment Of Bile Salt Hydrolasessupporting
confidence: 59%
“…Among them, bile acids combined with glycine or taurine, and then flow into the intestine through the gallbladder to participate in the emulsification of dietary fat and promote absorption. Conjugated bile acids first generate cholic acid and chenodeoxycholic acid under the action of intestinal bacterial bile acid hydrolase, and then generate 7-deoxycholic acid and lithocholic acid under the action of bile acid 7α dehydroxylase ( 78 80 ). Most of the bile acids in the intestine are actively absorbed and passively diffused into the liver through the portal vein, and the rest are excreted in the feces.…”
Section: Probiotics Diversely Involved In Lipid Metabolism To Improve...mentioning
confidence: 99%
“…Several probiotic strains have been extensively studied and their benefits to human health have been widely documented. For example, it has been reported that probiotics, such as Bifidobacterium longum , Lactobacillus acidophilus , L. casei, L. plantarum , exhibit bile salt hydrolases ( 42 , 72 74 , 80 , 81 ). For example, L. casei pWQH01, which overexpresses bsh 1 from L. plantarum AR113, appear to improve steatosis in vitro in a BSH-dependent manner ( 81 ).…”
Section: Probiotics Diversely Involved In Lipid Metabolism To Improve...mentioning
confidence: 99%
“…Strains of Lpb. plantarum (and/or its bioactive products), having an ability to ferment a broad spectrum of plant carbohydrates [ 119 ], probiotic effects on human [ 67 , 150 , 151 ] and animal health [ 48 , 120 , 152 ], as well as being found in dairy products [ 152 , 153 ], vegetables [ 154 ], sauerkraut, pickles, some cheeses, fermented sausages, fish products [ 155 ] and rhizospheric soil [ 156 ], are probably the best candidates for “One Health” probiotics (and for “One Health—tomato” probiotics). According to Table 2 , the strains of L. acidophilus , L. delbrueckii , Lcb.…”
Section: Probioticsmentioning
confidence: 99%